Effects of transcranial direct current stimulation combined with motor relearning program on strength and balance in stroke patients - Muhammad Hamad Haleem; Mirza Obaid Baig; Turki Abualait; Woo-Kyoung Yoo; Sumaiyah Obaid; Shahid Bashir (PeerJ)
Background A stroke is characterized by neurological deficits that result in compromised muscle strength and balance, impacting the overall wellbeing of the patient, including decreased quality of life, socialization and participation in daily activities. The aim of the study is to determine the effects of transcranial direct current stimulation combined with a motor relearning program on strength and balance in sub-acute stroke patients. Methods The randomized controlled trial involved 44 subacute stroke patients, randomly assigned to either the experimental group (n = 22) or control group (n = 22). The intervention included anodal transcranial direct current stimulation (tDCS) for the experimental group and sham stimulation with a motor relearning program for the control groups. Assessments were conducted using manual muscle testing for muscle strength and the Berg Balance Scale for balance at baseline, the fourth week, and the eighth week. Results There were no statistically significant effects in the experimental group for either strength or balance (p-value > 0.05) but there were time effects for both variables especially during the intervention period in both the experimental and control groups. Conclusion There does not appear to be any short term or long-term additional effects of anodal transcranial direct current stimulation on strength and balance in subacute stroke patients.